PENGARUH PENDEKATAN PROBLEM-BASED LEARNING (PBL) BERBASIS MULTIPLE INTELLIGENCES TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA PADA MATERI PECAHAN KELAS IV SEMESTER 2 - Hasanah, Lia Amaliati; Sudin, Ali; Maulana, M. (Jurnal Pena Ilmiah, 2017)
The low ability of mathematical problem solving of students, particularly at the elementary school students (elementary school) became the background of this research. In addition, a variety of characteristics shared by every student also observed in this study. One of the characteristics is intelligence. The fact that Howard Gardner suggested that everyone has diverse intelligence within him. Therefore, this research will apply the approach to Problem-Based Learning-based Multiple Intelligences as an effort to increase the ability of the mathematical problem solving of students which will also involve a variety of intelligence on the student in accordance with the theory of Multiple Intelligences by Howard Gardner expressed. The research method used experimental with control group pretest-postest design.Â The population in this study are all the students scattered throughout the elementary school Sub Kadipaten Regency, which is included into the Group of papak (medium). The sample of this research is the grade IV SDN Liangjulang VI that has two groups of study, so that the class IV A chosen as an experimental class and class IV B as the class of the control. The results of this study showed that after a given learning using approaches to Problem-Based Learning-based Multiple Intelligences and conventional approaches to increasing the ability of the mathematical problem-solving of students withÂ n-gain that experience an increase in the category are for class experiments and low categories of the class of the control. Improvement of mathematical problem solving ability get learning by using Problem-Based Learning approach-based Multiple Intelligences is better than students who get conventional learning. It is based on the results of different trials the average n-gain from the second class. In addition, based on the ANOVAÂ test one line on the sixth Multiple Intelligences smarts group indicates that is not the case of the difference of the average increase in the ability of problem-solving on the sixth group of the intelligence.